The intergenerational effects of worker displacement - Oreopoulos, Philip; Page, Marianne E.; Stevens, Ann Huff (National Bureau of Economic Research, 2005)
"This paper uses variation induced by firm closures to explore the intergenerational effects of worker displacement. Using a Canadian panel of administrative data that follows almost 60,000 father-child pairs from 1978 to 1999 and includes detailed information about the firms at which the father worked, we construct narrow treatment and control groups whose fathers had the same level of permanent income prior to 1982 when some of the fathers were displaced. We demonstrate that job loss leads to large permanent reductions in family income. Comparing outcomes among individuals whose fathers experienced an employment shock to outcomes among individuals whose fathers did not, we find that children whose fathers were displaced have annual earnings about 9% lower than similar children whose fathers did not experience an employment shock. They are also more likely to receive unemployment insurance and social assistance. The estimates are driven by the experiences of children whose family income was at the bottom of the income distribution, and are robust to a number of specification checks"--National Bureau of Economic Research web site.
Keywords: Displaced workers -- Canada; Income distribution -- Canada; Intergenerational relations -- Canada; Kanada